2020
DOI: 10.14429/dlsj.5.14656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Altitude on the Phenology and Fruit Quality Attributes of Apricot (Prunus armeniaca L.) Fruits

Abstract: Consumer concern about poor taste of fresh apricots is increasing and knowledge about the more suitable production requirement is essential. Genetic component influencing apricots quality is well known. However, there is limited information on environmental effect on fruit quality. This study aims to evaluate influence of altitude on phenological and fruit quality characters of apricot genotypes. Fruits from 162 genotype were collected from nine locations from 3006-3346 m asl in trans-Himalaya. The altitude ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In apple, the effect of altitude has been focused on in studies of physical and chemical parameters [19][20][21], and only very few works concentrated on sensory evaluation by using consumers or trained panels, such as Charles et al, who studied sensory attributes at different locations on one single apple variety [22]. Altitudes had a reported influence on aroma compounds [13,14,23], but there was a lack of information on its influence on apple VOCs. Anyway, it seems that compared with environment, year of production, and storage time, the variety is a more important source of compositional variations [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In apple, the effect of altitude has been focused on in studies of physical and chemical parameters [19][20][21], and only very few works concentrated on sensory evaluation by using consumers or trained panels, such as Charles et al, who studied sensory attributes at different locations on one single apple variety [22]. Altitudes had a reported influence on aroma compounds [13,14,23], but there was a lack of information on its influence on apple VOCs. Anyway, it seems that compared with environment, year of production, and storage time, the variety is a more important source of compositional variations [24].…”
Section: Introductionmentioning
confidence: 99%
“…Aroma is influenced not only by genetic differences and maturity but also by environmental factors [ 11 , 12 , 13 ]. Changing altitude of grow locations has an impact on temperature, humidity, pressure, ultraviolet radiation, sun exposure, wind, and geology [ 14 ]. Due to the complexity of the interactions between fruit development and environment, little information is available regarding the effects of these factors on fruit quality.…”
Section: Introductionmentioning
confidence: 99%
“…These results denote that the geographical conditions at WM (higher altitude) are the most suitable for producing higher nutritional and therapeutical dragon fruits. Concordantly, Naryal et al found that the weight of apricot fruits decreased with elevation, while the water content increased with the decrease in altitude [ 48 ]. It is also demonstrated that the sweetness of blueberry fruits increases with altitude, and fruits from low-altitude areas are more acidic [ 49 ].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the exceptional environmental conditions typical of this valley affect pomological traits such as fruit weight. Indeed, Naryal et al [53] reported that the apricot fruit weight decreases by 0.5 g for every 100 m of increase in altitude. Since in our study a significant difference emerged for the fruit weight parameter (i.e., greater fruit size in low planting density), we took this aspect into account to calculate a differentiated picking productivity in the economic analysis (Figure 10).…”
Section: Discussionmentioning
confidence: 99%